Bismuth ferrite based acetone gas sensor: evaluation of graphene oxide loading - Ghadage, Pandurang; Shinde, K. P.; Nadargi, Digambar; Nadargi, Jyoti; Shaikh, Hamid; Alam, Mohammad Asif; Mulla, Imtiaz; Tamboli, Mohaseen S.; Park, J. S.; Suryavanshi, Sharad (RSC Advances, 2024)
We report a BiFeO3/graphene oxide (BFO/GO) perovskite, synthesized using a CTAB-functionalized glycine combustion route, as a potential material for acetone gas sensing applications. The physicochemical properties of the developed perovskite were analysed using XRD, FE-SEM, TEM, HRTEM, EDAX and XPS. The gas sensing performance was analysed for various test gases, including ethanol, acetone, propanol, ammonia, nitric acid, hydrogen sulphide and trimethylamine at a concentration of 500 ppm. Among the test gases, the developed BFO showed the best selectivity towards acetone, with a response of 61% at an operating temperature of 250 degrees C. All the GO-loaded BFO samples showed an improved gas sensing performance compared with pristine BFO in terms of sensitivity, the response/recovery times, the transient response curves and the stability. The 1 wt% GO-loaded BiFeO3 sensor showed the highest sensitivity of 89% towards acetone (500 ppm) at an operating temperature of 250 degrees C. These results show that the developed perovskites have significant potential for use in acetone gas sensing applications. CTAB-functionalized glycine combustion yields BiFeO3/graphene oxide (BFO/GO) perovskite for acetone gas detection.

Reduced graphene oxide/tungsten oxide (rGO/WO3): a versatile nanocomposite for enhanced detection of acetone - Patil, Abhijeet P.; Gaikwad, Mayur A.; Nadargi, Jyoti D.; Shaikh, Hamid; Alam, Mohammad Asif; Tamboli, Mohaseen S.; Kim, Jin Hyeok; Mulla, Imtiaz S.; Suryavanshi, Sharad S. (Journal of Materials Science-Materials In Electronics, 2024)
In this study, we report a straightforward method for synthesizing semi-cubical nanostructures of tungsten trioxide (WO3) loaded with reduced graphene oxide (rGO) via a hydrothermal approach. Furthermore, the systematic investigations were made towards the improved gas sensing capabilities of these nanostructures for acetone. The use of semi-cubical rGO/WO3 nanostructures demonstrate the provision of efficient gas diffusion routes via a meticulously arranged mesoporous framework. Hence, it leads to a significant improvement in the sensing response towards acetone. The analysis of the sensing capabilities demonstrates that the response of the sensor is influenced by variations in operating temperature and gas concentration. It is seen that the inclusion of rGO not only enhances the sensing response but also gives quick response and recovery, which are measured to be 12 and 33 s, respectively. The WO3 sensor loaded with 0.1 wt% rGO demonstrates a discerning reaction to acetone, exhibiting a high response of 93.60% than that of the unmodified WO3 sensor (76.30%). The gas sensing properties are explained through the role of rGO and the structural and morphological properties of the developed nanostructures.